An introduction to non-archimedean functional analysis - Śliwa, Wiesław (My University, 2010)
A mini-course on the structure of Banach and Frechet spaces over non-archimedean fields
This mini-course has been presented at the Workshop On Non-Archimedean Functional Analysis, Lie Groups and Dynamical Systems, University of Paderborn, Germany, February 8-12, 2010
Keywords: Non-archimedean Frechet spaces